2016
DOI: 10.1097/wnp.0000000000000241
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular Ultrasound in the Assessment of Polyneuropathies and Motor Neuron Disease

Abstract: Neuromuscular ultrasound is an emerging technology for the evaluation of conditions affecting nerve and muscle, with the majority of research focusing on focal neuropathies. Despite this focus, researchers have also investigated the ultrasonographic changes that occur in the nerves and muscles of those with more diffuse polyneuropathies and motor neuron diseases, and this review will detail the findings in these conditions. Specific findings are discussed in this paper, but general themes will also be presente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…23 Separately, ultrasound may also assist with identifying the most appropriate nerve to biopsy and possibly improve diagnostic yield. 24 In conclusion, stepwise progression and, in the case of systemic vasculitis, the presence of selected autoantibodies are strong discriminators between pathologically proven and pathologically unlikely vasculitis. Chronic, symmetric symptoms, upper limb-dominant symptoms, pure motor presentations, NCS findings that are normal or predominantly demyelinating, and Table S1 in Supplementary Material online, adapted from Hadden et al).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…23 Separately, ultrasound may also assist with identifying the most appropriate nerve to biopsy and possibly improve diagnostic yield. 24 In conclusion, stepwise progression and, in the case of systemic vasculitis, the presence of selected autoantibodies are strong discriminators between pathologically proven and pathologically unlikely vasculitis. Chronic, symmetric symptoms, upper limb-dominant symptoms, pure motor presentations, NCS findings that are normal or predominantly demyelinating, and Table S1 in Supplementary Material online, adapted from Hadden et al).…”
Section: Discussionmentioning
confidence: 93%
“…A small study comparing patients with vasculitis to patients with noninflammatory axonal neuropathy showed that sonographic enlargement of arm nerves proximal to sites of nerve compression accurately identified patients with vasculitis with a sensitivity of 94% and specificity of 88% . Separately, ultrasound may also assist with identifying the most appropriate nerve to biopsy and possibly improve diagnostic yield …”
Section: Discussionmentioning
confidence: 99%
“…Over the past 20 years, ultrasound has played an increasing role in the evaluation of many neuromuscular disorders, with its main application being in the evaluation of nerve health . For example, it has been found to be highly sensitive to carpal tunnel syndrome (CTS) and ulnar neuropathy, but has also been valuable in identifying areas of nerve inflammation, localized injury, compression, and tumors …”
mentioning
confidence: 99%
“…increasing role in the evaluation of many neuromuscular disorders, with its main application being in the evaluation of nerve health. 1 For example, it has been found to be highly sensitive to carpal tunnel syndrome 2 (CTS) and ulnar neuropathy, 3 but has also been valuable in identifying areas of nerve inflammation, 4,5 localized injury, 6 compression, 7 and tumors. 8,9 In addition to its use for nerve evaluation, ultrasound has also been studied as a way of quantifying muscle condition.…”
mentioning
confidence: 99%
“…When moved proximally to assess the median nerve at a noncompressive site (forearm), there was no difference in CSA between CIPN patients and healthy controls. This discrepancy is often seen with NMUS evaluation of symptomatic carpal tunnel syndrome and other polyneuropathies . These findings suggest that, at compression sites, CIPN may aggravate nerve entrapment and cause an increase in CSA of peripheral nerves.…”
Section: Discussionmentioning
confidence: 97%